Impact properties of glass fiber/epoxy composites at cryogenic environment. (1st May 2016) - Ma, Hei-lam; Jia, Zhemin; Lau, Kin-tak; Leng, Jinsong; Hui, David
Abstract: Glass fiber/epoxy polymer (GFRP) composites are widely used in the aerospace engineering industry due to their high specific strength to weight ratio with non-corrosive properties, however they are very sensitive to foreign object impact. This study aims at investigating the impact response of GFRP composites at different temperature environments, which are encountered in their service at high attitude and low earth orbit (LEO) conditions. 18 GFRP samples were fabricated by vacuum infusion process and 9 of them were post-cured at 353 K for 3 h to ensure that a complete chemical reaction inside the samples was achieved. Low velocity drop weight test was performed for the samples prepared and then stored at room temperature (295 K), dry ice temperature (199 K) and liquid nitrogen temperature (100 K) conditions. The apparent damages and their size were visually examined and measured. Impact parameters such as impact load, deflection and energy absorption of each damage type were also analyzed. Besides, the post-curing effect was also studied to verify its significance to the impact properties of composites. Experimental results showed that GFRP composites at cryogenic condition exhibited smaller apparent damage and were stiffer as compared with other cases. However, they demonstrated relatively poor energy absorbability at low temperature condition. It was also found that post-curing could reduce the apparent damage and increase the energy absorption of GFRP composites.